Sex & God how religion distorts sexuality - Ray, Darrel (Bonner Springs, Kan. : IPC Press, 2012)
Why are all the major religions consumed with sex? What makes sex so important whether Buddhism or Islam, Christianity or Mormonism? What is the impact of religion on human sexuality. This book explores this and more. It ventures into territory that has never been examined. You will be surprised at how much religion has influenced your sexuality, who you marry, the pleasure you get or don't get from sex and what you can do about it.
Section 1. Religion in perspective -- section 2. Follow the biology -- section 3. Follow the culture -- section 4. The psychology of religion and sex -- section 5. Program yourself for a change.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sex -- Religious aspects; RELIGION / Atheism; RELIGION / Sexuality & Gender Studies; Electronic books